EVALUASI PELAKSANAAN PROGRAM PENCEGAHAN DAN PENGENDALIAN KASUS DEMAM BERDARAH DENGUE DI DINAS KESEHATAN KOTA PEKANBARU TAHUN 2018 - AMRONI AMRONI RONI (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2018)
In 2016 cases of Dengue Hemorrhagic Fever (DHF) in Pekanbaru were the highest case and Pelalawan District was the lowest case. An increase in the number of cases of several years of the implementation of the DHF Prevention and Control program (P2) has not been carried out optimally, the implementation of these activities needs to be evaluated. The research objective is to evaluate the input and process of implementing DBD P2 program. The study was conducted on 16 July - 16 August 2018 at the Pekanbaru City Health Office.This type of qualitative research and Rapid Assessment Prosedures research design and informants amounted to 7 people. The results of the input research were not enough human resources, 3 units of fogging machines were damaged and 1 car unit was not suitable for use. Whereas the process obtained obstacles to the implementation of PSN and PE namely the existence of communities that are difficult to find, obstacles to the implementation of larvicidation, fogging and periodic larva monitoring, namely the existence of communities who are not willing, and obstacles in implementing counseling that is difficult to collect citizens. It can be concluded that the DBD P2 program has not been implemented optimally by the Pekanbaru City Health Office. It is recommended that there be additional staff and procurement of new cars, for officers to carry out program activities that have not been carried out, so that they are carried out again so that the activities are carried out thoroughly, and conduct regular evaluations or through coordination meetings for all parties involved in the implementation of DBD P2 program activities.